Effect of treating the titanium electrode of the desalination performance in microfluidics system - Heng, J. T.; Abdulbari, Hayder A. (IOP Publishing, 2020)
The commercially applied macro desalination methods such as reverse osmosis, multi-stage flash distillation and multi-effect distillation suffer from several drawbacks such as high power consumption and low separation performance.It is believed that the micro-scaled structures will optimize the mixing efficiency of the micro-flow liquid and lead to higher desalination performance. Large surface-area-to-volume ratio in micro-scale promotes the fluids interaction since the laminar flow properties in the microfluidic device allowing the high-velocity gradients and dominant interfacial effects which is the manipulation of fluid streams [1]. The present work introduces a microfluidics chip for water desalination which fabricated using polydimethylsiloxane soft lithography method. Three layers of polydimethylsiloxane (PDMS) were fabricated using soft lithography method where PDMS liquid mixture was mixed and poured onto the designed wafer and heated to become solid. The solid PDMS was then peeled off from the wafer and hence assembled together with another PDMS by using surface plasma treatment process. The flow rate was set at 90 mL/h and the system was supplied with 9 V of potential difference. Aluminium and titanium were being used as the electrodes which achieved 65% and 15% of salt removal efficiency, respectively. Titanium was further treated by using the etching method and the performance was studied. The desalination efficiency was analyzed and evaluated with the flow rate of 90mL/h using capacitive deionization method. The result revealed that the performance of untreated titanium was better than the treated titanium which achieves 10% improvement in salt removal efficiency. The finding in this work show that the desalination efficiency was relied on the electrode surface property where the oxide layer inhibits the deionization from occurs.